2015
DOI: 10.1177/1358863x14566430
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and central hemodynamic changes following exercise-induced heat stress

Abstract: This study examined the effects of moderate exercise-induced heat stress (EIHS) on vascular function, central hemodynamic load and indices of coronary perfusion. Vascular-hemodynamic measures were collected in 12 healthy men (aged 22±3 years) pre and post 100 minutes of moderate, intermittent exercise in two randomized conditions: heat stress (HS; wearing firefighter personal protective equipment (PPE)), and no heat stress (NHS; wearing a cooling shirt and equivalent PPE weight). Aortic blood pressure, reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
(69 reference statements)
1
14
0
Order By: Relevance
“…[12][13][14] Additionally, it has been shown that HR response and cardiovascular strain are increased during exercise in a hot and humid environment and that this is attenuated with the use of a CD. [13][14][15][16] Weight loss has also been shown to be reduced when using a CD during exercise in the heat. 16,17 Previously, PCM CDs have been reported to offer a cooling effect that is "quick and strong," mimicking the results seen in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Additionally, it has been shown that HR response and cardiovascular strain are increased during exercise in a hot and humid environment and that this is attenuated with the use of a CD. [13][14][15][16] Weight loss has also been shown to be reduced when using a CD during exercise in the heat. 16,17 Previously, PCM CDs have been reported to offer a cooling effect that is "quick and strong," mimicking the results seen in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that exposure to heat, associated with increased body temperature, increases the peripheral arterial compliance, shear stress and blood flow [ 5 , 6 ]. Exercise also increases the body temperature and evokes a number of hemodynamic changes, including vasodilation [ 7 ]. Above all, these results demonstrate an immediate and possibly transient effect of exercise and increased body temperature on the cardiovascular physiology.…”
Section: Introductionmentioning
confidence: 99%
“…Blood pressures (systolic, diastolic and mean arterial pressure) were examined pre‐ and postexercise and were not different between conditions, suggesting that the blood pressures at which the FMD measurements were made were not likely to be a contributing factor to the reduction in vascular function in response to EIHS (Lefferts et al . ). Although no direct measures of sympathetic activity were assessed in this study, heart rate remained significantly elevated postexercise in the EIHS trail, suggestive of less parasympathetic tone and a greater unveiling of sympathetic nerve activity.…”
Section: Discussionmentioning
confidence: 97%
“…; Lefferts et al . ) and in vitro (Ives et al . ), peripheral vascular function in relation to heat stress has remained largely unstudied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation